2022
DOI: 10.1073/pnas.2114545119
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of early or late exposure to prenatal maternal immune activation on mouse embryonic neurodevelopment

Abstract: Significance Prenatal exposure to maternal infection increases the risk of developing mental health disorders, such as schizophrenia and autism spectrum disorder. Exposure to maternal immune activation has been associated with a number of neuroanatomical deficits in adolescent and adult offspring, with differing effects based on the gestational timing of infection. However, little is known about how the embryo brain is affected. We show, using whole-brain MRI, that maternal immune activation signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…While dark microglia were previously reported at adulthood in several mouse models of pathology (e.g., prenatal and maternal immune activation, middle-aged APP-PS1, chronic stress, CX3CR1 knockout, R6/2 model of Huntington's disease; [64,78,94,105,106]), their presence in the human brain had yet to be reported. We observed dark cells possessing ultrastructural features of dark microglia in the hippocampal head of post-mortem brain samples from a 49-year-old man and in the parahippocampal gyrus from an 81-year-old woman (both with a post-mortem interval of 18 h).…”
Section: Dark Microglia Are Found In Human Post-mortem Brain Samples ...mentioning
confidence: 99%
“…While dark microglia were previously reported at adulthood in several mouse models of pathology (e.g., prenatal and maternal immune activation, middle-aged APP-PS1, chronic stress, CX3CR1 knockout, R6/2 model of Huntington's disease; [64,78,94,105,106]), their presence in the human brain had yet to be reported. We observed dark cells possessing ultrastructural features of dark microglia in the hippocampal head of post-mortem brain samples from a 49-year-old man and in the parahippocampal gyrus from an 81-year-old woman (both with a post-mortem interval of 18 h).…”
Section: Dark Microglia Are Found In Human Post-mortem Brain Samples ...mentioning
confidence: 99%
“…More recent studies continue to highlight the importance of prenatal timing in poly I:C‐induced MIA models 45,196,197 . A central theme in these studies is the temporally regulated impairment of GABAergic interneuron subtypes.…”
Section: Future Perspectives and Considerations For Mia Modelingmentioning
confidence: 99%
“…These studies are further motivated by recent observations that offspring exposed to MIA (modeling the exposure to maternal infection during pregnancy, a known risk factor for neurodevelopmental disorders) show litter-dependent variance in resilience and susceptibility to the risk factor exposure (Mueller et al, 2021). However, our group also demonstrated that the gestational timing of MIA-exposure could further modulate neurodevelopmental outcomes (Guma, do Couto Bordignon, et al, 2021; Guma et al, 2022; Guma, Snook, et al, 2021). At an even more basic level, litter-dependent modulation of body and brain weight have been reported using linear and linear mixed-effect models; these effects are further affected by sex (Golub & Sobin, 2020; Jiménez & Zylka, 2021).…”
Section: Introductionmentioning
confidence: 68%